Assessment of In‐Season Soil Nitrogen Tests for Corn Planted into Winter Annual Cover Crops. Issue 6 (18th October 2018) - Norris, Robert; Chim, Bee Khim; Evanylo, Gregory; Reiter, Mark; Thomason, Wade
Abstract : Core Ideas: The Solvita 1‐d CO2 mineralization test could be a new tool to improve in‐season N rate recommendations for corn. Solvita and soil NO3 –N tests may be useful for predicting the level of early‐season N mineralization from winter cover crops (WCCs). Soil NO3 –N collected at the V4 growth stage of corn at 0 to 15 cm was positively correlated ( R 2 = 0.45) with corn check yield. Neither the Solvita nor the presidedress nitrate test detected WCC N mineralization consistently enough to use them in rate recommendations. Environmental and economic goals encourage the use of soil N tests to improve fertilizer N (FN) management in corn ( Zea mays L.). Recently, the Solvita 1‐d CO2 burst test, which proposes to estimate soil potentially mineralizable N (PMN), has been promoted as a tool for FN recommendations. We aimed to compare the Solvita test with the established presidedress nitrate test (PSNT) for estimating optimum sidedressed FN rates in a typical corn crop rotation in the Mid‐Atlantic United States that includes winter annual cover crops (WCCs). Research was conducted at eight locations from 2012 to 2014. Three WCC treatments [cereal rye ( Secale cereale L.), hairy vetch ( Vicia villosa Roth ssp. villosa ) or a cereal rye–hairy vetch mix] were the main plots and 10 FN rates were the subplots. The WCCs affected preplanting (PP) Solvita results at one location, V4 NO3 –N at 0 to 15 cm (PSNT15) at four locations, and V4 NO3 –N at 0 to 30 cm (PSNT30) at two locations. Correlations between soil N test parameters and relative corn yields ranged from 0.31 to 0.13. Values for PSNT15 and PSNT30 correlated positively with corn check yields ( r = 0.41 and 0.39 respectively). Solvita did not provide additional information to PSNT for predicting preplanting PMN, V4 PMN, or corn check yields. The advantages of the Solvita test were its simplicity, speed of analysis, and lower coefficient of variation relative to the PSNT. Neither method was consistently effective for predicting WCC effects on soil N or relative corn yield.